2017
DOI: 10.1136/bmjopen-2017-017713
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, risk factors and perinatal outcomes for placenta accreta in Australia and New Zealand: a case–control study

Abstract: ObjectiveEstimate the incidence of placenta accreta and describe risk factors, clinical practice and perinatal outcomes.DesignCase–control study.SettingSites in Australia and New Zealand with at least 50 births per year.ParticipantsCases were women giving birth (≥20 weeks or fetus ≥400 g) who were diagnosed with placenta accreta by antenatal imaging, at operation or by pathology specimens between 2010 and 2012. Controls were two births immediately prior to a case. A total of 295 cases were included and 570 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
100
2
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(124 citation statements)
references
References 31 publications
17
100
2
5
Order By: Relevance
“…The incidence of placenta accreta in the USA is approximately 1 in 500 pregnancies, 22 which is higher than reported incidences of 1.7 per 1000 pregnancies in England 23 and 4.4 per 10 000 pregnancies in Australia. 24 The increased accreta rate in the USA likely also contributed to the increased rates of PPH and associated complications.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of placenta accreta in the USA is approximately 1 in 500 pregnancies, 22 which is higher than reported incidences of 1.7 per 1000 pregnancies in England 23 and 4.4 per 10 000 pregnancies in Australia. 24 The increased accreta rate in the USA likely also contributed to the increased rates of PPH and associated complications.…”
Section: Discussionmentioning
confidence: 99%
“…There were 22 retrospective studies 14, and seven prospective. 19, [47][48][49][50][51][52] Twenty-eight (28/29) were published after the year 2000 (Table 1). There were 18 studies from a single institution 14,[26][27][28][29][30][31]33,[36][37][38][39][40]42,44 , three involving two affiliated institutions 32,34,51 , two studies from the National Institute of Child Health and Human Development Maternal-Fetal Medicine Units Network 48,50 , two regional studies 43,46 , three national studies 41,45,49 and two international studies involving four 19 and two 52 countries, respectively.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The clinical criteria described by the authors for the clinical diagnosis of placenta accreta spectrum at delivery felt into three categories (Table 2): basic description 32,34,35,[38][39][40]44,47,48,50,51 ; extended description 27,30,33 ; and World Health Organization (WHO) international classification. 19,36,43,46 More than a third of the studies (11/29) 14,26,29,31,37,41,42,45,49,52 did not describe the clinical criteria used for the diagnosis of placenta accreta spectrum at birth. Lateral extension of the accreta areas and detailed description of the uterine vasculature anatomical changes associated with invasive placentation were not reported by any of the 29 studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…[New 2018] P All epidemiological studies of the last 2 decades have shown a direct association between the increase in caesarean deliveries and the incidence of placenta accreta spectrum (abnormally adherent and invasive placenta) in subsequent pregnancies worldwide. [111][112][113][114][115][116][117][118][119][120][121] The 2016 Nordic Obstetric Surveillance Study found that the risk of invasive placentation increases seven-fold after one prior caesarean section. 117…”
mentioning
confidence: 99%